Globalizing through the vernacular: Kothis, Hijras, and makingof quear and trans identities in India - Dutta, Aniruddha (New Delhi Bloomsbury, 2025)
Globalizing through the Vernacular analyzes the relation between dominant frameworks of LGBTQ+ identity in India and non-elite, non-metropolitan communities such as kothis and hijras, a spectrum of feminine-identified people usually assigned male at birth. Going beyond the well-known 'third gender' hijra community, this is the first book to study the discourses and practices of related but underrepresented groups like kothis and dhuranis in small-town and rural India while simultaneously examining their relation to and role within LGBTQ+ identity politics.